Development of Project-Based Learning Materials for Basic Physics to Enhance Students' Critical Thinking Skills - Usman, Usman; Setiawan, Trisno; Khaeruddin, Khaeruddin (Universitas Muhammadiyah Makassar, 2025)
The rapid advancement of education in the era of Industrial Revolution 4.0 demands the mastery of critical thinking as a core competency for students. However, physics learning at the tertiary level still tends to be teacher-centered, resulting in low levels of critical thinking skills. This study aimed to develop Project-Based Learning (PjBL) teaching materials to enhance students’ critical thinking abilities in physics, specifically in kinematics. The research employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate). Participants were physics education students at Makassar State University in the 2024/2025 academic year. Data were collected through expert validation sheets, student response questionnaires, project performance assessments, and critical thinking skill tests, and then analyzed using descriptive, quantitative, and qualitative approaches. The results showed that expert validation of the developed teaching materials reached an average of 96.96% (very valid), while student responses obtained 91.71% (very positive). Students’ project creation ability achieved an average score of 84.25 (in the good category). Critical thinking skills improved significantly, with pretest and posttest averages of 56.7 and 84.3, respectively, and an N-Gain score of 0.63 (moderate improvement). The novelty of this research lies in integrating PjBL into structured teaching materials that directly target critical thinking indicators, which were not thoroughly addressed in prior studies. In conclusion, the developed PjBL-based teaching materials are valid, practical, and effective in fostering critical thinking, and they provide an innovative contribution to physics education by offering a model that prepares students to meet 21st-century academic and professional challenges.